Criança e adolescente: gênero e sexualidade um debate necessário - Martins, Eunice Emanuele Soares (IFCHS - Instituto de Filosofia, Ciências Humanas e Sociais, 2022)
This work is a bibliographical and documentary research of secondary source, of critical bias and explanatory nature and with emphasis on qualitative data, the result of a Scientific Initiation Project. Where the discussion about the social history from childhood to the present day passes, general notes on the discussion of gender, sexuality and childhood and, finally, the research result. The objective of this research was to map the scientific productions in the areas of Social Work, Psychology, Education and Sciences of Religion and Theology, in order to point out the conceptions and tendencies of the theme of children, adolescents, gender and sexuality.